Membuka Pintu Rezeki dalam Perspektif Al-Qur’an - Basri Mahmud; Hamzah Hamzah (Institut Agama Islam Negeri (IAIN) Curup, 2020)
Opening the Doors of Sustenance in the Perspective of the Qur’an This study aimed to reveal the meaning of the word ar-rizq alongside its variants in the Qur'an. Also, this study sought to know the doors of sustenance resting upon the signs in the Qur'an. This study used a thematic method (mawdhu'i) with the term and conceptual thematic model in order to reveal the doors of sustenance from the Qur’anic verses associated with the term ar-rizq. The primary data of this study were the Qur’anic data, namely the Qur’anic verses closely associated with the word ar-rizq in the form of clauses, phrases, and words. Meanwhile, the secondary data were in the form of notions, ideas, and interpretations of the interpreters. The results of this study indicated that the word ar-rizq with its variants is repeated 123 times in the Qur'an, namely 61 times in the form of fi'il and 62 times in the form of isim, which are scattered in 41 Surahs in the Qur'an. The meaning of ar-rizq is all gifts from Allah to all His creatures. Subsequently, the doors of sustenance based on the Qur’anic signs include: guaranteed sustenance, sustenance earned through efforts, sustenance due to istighfar, sustenance due to gratitude to Allah, sustenance for giving alms, and sustenance for devotion to Allah.